Impact of Climate Change and Dry-Salting Preservation on Histamine Levels in Three Marine Fish Species - Khashroum, Ashraf Omar (Jordan Journal of Agricultural Sciences, 2022)
This study was conducted to estimate the concentrations of histamine in three species of marine fish (fresh and preserved with dry salting). No significant differences (p ≥ 0.05) in histamine concentrations were found among the Chirocenterus dorab, Scomberoides commersonianus, and Xiphias gladius fish species during summer or winter. On the other hand, the mean concentrations of histamine differed significantly (p < 0.05) between summer and winter in the fresh samples of the aforementioned fish species. In the case of the salted fish species, no significant differences (p ≥ 0.05) in histamine concentrations were detected in Chirocentrus dorab under all salt treatments (5%, 10%, 15%, and 20%). In contrast, significant differences (p < 0.05) in histamine concentrations were found between the two NaCl treatments of 5% and 20% in the Scomberoides commersonianus fish samples